OPTIMALISASI KEMAMPUAN MEMBACA AL-QUR'AN MELALUI PEMAHAMAN QS. AL-FIL DAN QS. AL-MA’UN DI SANGGAR BELAJAR GOMBAK UTARA, SELANGOR, MALAYSIA - Itmam Aulia; Zaki Mubarok; Husna; Nur Fatikhatun Niami (Universitas Bina Taruna Gorontalo, 2024)
This research aims to describe a program to improve the ability to read the Koran for Indonesian citizen (WNI) children at the North Gombak Learning Studio (SB), Selangor, Malaysia. This program is carried out by lecturers and students of the Bakti Negara Islamic Institute (IBN) Tegal, Central Java, as part of community service carried out abroad. The aim is to foster love and improve the ability to read the Koran properly and correctly for Indonesian citizens who live in Malaysia but do not have complete documents as a requirement for citizenship. The method used in this program is the presentation of material about makharijul letters to help children understand how to pronounce the letters in the Koran correctly. Next, memorize the Al-Qur'an letters al-Ma'un and al-Fil and their meanings to improve memorization and understanding of the contents of the Al-Qur'an. The final stage is watching a motivational video from a blind memorizer of the Koran to provide inspiration and enthusiasm for children to continue learning and memorizing the Koran. The data collection technique used in this research is observation, by directly observing program activities and children's participation. Conduct interviews with children, parents, and teachers to find out their experiences and perceptions of the program. Finally, a memorization test by carrying out a memorization test of al-Ma'un and al-Fil letters to determine the level of children's memorization before and after the program. The results of the discussion show that this program is effective in fostering love and improving the ability to read the Koran for Indonesian children in SB Gombak Utara, Selangor, Malaysia.